A Book Made of Steel: Rereading the Technological History of Europe’s “Long 20th Century” (KULT_online, 2017)
Writing the Rules for Europe. Experts, Cartels, International organizations is the fifth out of six books from the series Making Europe: Technology and Transformations, 1850-2000. As such, it offers to the readers a new perspective on our understanding of Europe and challenges many well-established truths in contemporary Western historiography. The work of Johan Schot and Wolfram Kaiser switches the focus from political to technological history. It redirects our attention from the politicians and diplomats to the international experts, engineers, specialists, businessmen, lobbyists, and innovators. Failing to take them into consideration, as the authors argue, risks profoundly limiting our understanding of European integration, European organizations, and even the European Union itself. Writing the Rules for Europe. Experts, Cartels, International organizations is a guide to the long-term processes which continue to shape the European presence and its future.